Dissipation of triclosan, triclocarban, carbamazepine and naproxen in agricultural soil following surface or sub-surface application of dewatered municipal biosolids - Al-Rajab, Abdul Jabbar; Sabourin, Lyne; Lapen, David R.; Topp, Edward (The Science of the total environment, 2015)
In many jurisdictions land application of municipal biosolids is a valued source of nutrients for crop production. The practice must be managed to ensure that crops and adjacent water are not subject to contamination by pharmaceuticals or other organic contaminants. The broad spectrum antimicrobial agents triclosan (TCS) and triclocarban (TCC), the anti-epileptic drug carbamazepine (CBZ), and the nonsteroidal anti-inflammatory drug naproxen (NAP) are widely used and are carried in biosolids. In the present study, the effect of biosolids and depth of placement in the soil profile on the rates of TCS, TCC, CBZ, and NAP dissipation were evaluated under semi-field conditions. Aggregates of dewatered municipal biosolids (DMBs) supplemented with (14)C-labeled residues were applied either on the soil surface or in the subsurface of the soil profile, and incubated over several months under ambient outdoor conditions. The dissipation of TCS, TCC and NAP was significantly faster in sub-surface than surface applied biosolid aggregates. In contrast the dissipation rate for CBZ was the same in surface applied and incorporated aggregates. Overall, the present study has determined a significant effect of depth of placement on the dissipation rate of biodegradable molecules.